Adrenal insufficiency among children treated with hormonal therapy for infantile spasms. Issue 9 (8th July 2022) - Doré‐Brabant, Gabrielle; Laflamme, Geneviève; Millette, Maude; Osterman, Bradley; Chrestian, Nicolas
Abstract: Objective: Hormonal therapy is a standard treatment for children with infantile spasms. However, the high doses given and long treatment duration expose patients to the risk of adrenal insufficiency (AI). This study aims to quantify the cumulative incidence of AI among children with infantile spasms treated with high‐dose corticosteroids and/or adrenocorticotropic hormone. Methods: A retrospective chart review of patients treated for infantile spasms was performed between January 2009 and March 2020 in one pediatric specialized hospital. Variables collected include patient and treatment characteristics, risk factors of AI, and adrenal function testing. Analysis included descriptive statistics such as incidence and bivariate analysis. Results: Thirty‐one patients were included and received a total of 33 courses of treatment (17 corticosteroids [prednisone/prednisolone], 12 adrenocorticotropic hormone, and four combined). Physiologic hydrocortisone replacement therapy with stress supplementation was received after 32 of 33 (97%) courses of treatment. Adrenal function was assessed in 32 of 33 (97%) and AI occurred in 25 of 33 (76%, 95% confidence interval = 58–89). No predictive factor of AI was identified after hormonal treatment. No drug regimen was found to be safe. The two patients who developed an acute adrenal crisis presented to the emergency room within the days (between 2 and 7) following weaning off of hormonal treatment. They were the youngest children of the cohort, and both received prednisolone. Significance: Adrenal insufficiency is frequent and can potentially lead to an adrenal crisis in this population. This study highlights the necessity of hydrocortisone replacement therapy until AI has been excluded in a patient who has received hormonal therapy to treat infantile spasms. As such, routine laboratory assessment of adrenal function should be done in all patients.